2015
DOI: 10.1093/femsec/fiv162
|View full text |Cite
|
Sign up to set email alerts
|

Microbial composition of biofilms associated with lithifying rubble ofAcropora palmatabranches

Abstract: Coral reefs are among the most productive ecosystems on the planet, but are rapidly declining due to global-warming-mediated changes in the oceans. Particularly for the Caribbean region, Acropora sp. stony corals have lost ∼80% of their original coverage, resulting in vast extensions of dead coral rubble. We analyzed the microbial composition of biofilms that colonize and lithify dead Acropora palmata rubble in the Mexican Caribbean and identified the microbial assemblages that can persist under scenarios of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 66 publications
0
17
0
3
Order By: Relevance
“…The reef framework is continuously infilled with sediment, rubble and cements, as part of diagenetic alteration [ 42 , 65 , 66 ]. These cements are largely composed of high‐magnesium calcite and aragonite that can infill the voids between the rubble pieces and encrust over the dead skeletal materials [ 61 , 67 ]. Calcifying microbialites further trap and bind sediments and are important in providing a rigid cementation ( S2 Appendix ).…”
Section: The Structure and Consolidation Of Reef Substratamentioning
confidence: 99%
“…The reef framework is continuously infilled with sediment, rubble and cements, as part of diagenetic alteration [ 42 , 65 , 66 ]. These cements are largely composed of high‐magnesium calcite and aragonite that can infill the voids between the rubble pieces and encrust over the dead skeletal materials [ 61 , 67 ]. Calcifying microbialites further trap and bind sediments and are important in providing a rigid cementation ( S2 Appendix ).…”
Section: The Structure and Consolidation Of Reef Substratamentioning
confidence: 99%
“…Az oxigéntermelő és anoxigenikus (oxigént nem termelő) fototróf szervezetek CO 2 -megkötése nem jár alkalinitásnövekedéssel, de a folyamat során nő a pH, ami karbonátkiválást eredményez (PENTECOST & RIDING 1986, MERZ 1992. Azt is kimutatták, hogy a biofilm egyes részein is kialakulhat olyan alkalinitás-gradiens, amely elmeszesedést eredményez (PENTECOST 1985, BELTRÁN et al 2016. Bizonyos környezeti feltételek mellett azonban, pl.…”
Section: öSszefoglalásunclassified
“…Jelentős mértékben járulnak hozzá a zátonyszerkezet stabilitásának kialakításához (PERRY & HEPBURN 2008, BELTRÁN et al 2016. A nagy Mg-tartalmú kalcitból álló mikrobakérgeket a szakirodalom korábban többféle változat ban is említi, úgy mint mikritcement, mikrobás karbonátok, sztromatoli tok és mikrobialitok (JONES & HUNTER 1991, RIDING 1991b, MONTAGGIONI & CAMOIN 1993, CAMOIN et al 1999, RIDING & TOMÁS 2006, RIDING 2011, SEARD et al 2011, RIDING et al 2014, BELTRÁN et al 2016. Az indopacifikus és karibi térség negyedidőszaki zátonyrendszereiben is megfigyeltek mik ro ba kérge ket, amelyek általában a korallok elhalása után képződtek a zátonyok fejlődéstörténetének utolsó fázisában.…”
Section: Aktuálgeológiai Kutatások Korallzátonyokonunclassified
See 1 more Smart Citation
“…This process begins to create a new reef structure that increases in extension according to the deterioration of healthy Acropora palmata corals. Beltrán et al [17] suggested that microbial calcification in Acropora rubble can be induced in biofilms composed of extracellular polymeric substances (e.g. polysaccharides, proteins, lipids, nucleic acids) and a variety of microorganisms attached to coral rubble, becoming an important cementing agent.…”
Section: Introductionmentioning
confidence: 99%